Calorimetry of phase transitions in liquid crystal 8CB under shear flow. Issue 8 (3rd February 2023) - Yamamoto, Taro; Nagae, Yuki; Wakabayashi, Tomonari; Kamiyama, Tadashi; Suzuki, Hal
Abstract : A differential scanning calorimeter equipped with a shearing system was developed to elucidate the thermodynamic properties of liquid crystalline materials under shear flow, and the phase transitions of 8CB were investigated. Abstract : A differential scanning calorimeter equipped with a shearing system (shear rate of  < 400 s −1 ) was developed to elucidate the thermodynamic properties of liquid crystalline phase transitions under shear flow. An analytical method was proposed to accurately estimate the heat flow caused by shear friction to evaluate the transition entropies. The phase transitions of 4′- n -octyl-4-cyano-biphenyl (8CB) under shear flow were investigated using the developed calorimeter. Although several shear-induced transitions for 8CB have been reported in the past using viscosity and small-angle X-ray scattering (SAXS) measurements, only the nematic–isotropic (N–I) and smectic-A–nematic (SA –N) transitions were detected as heat flow peaks. The N–I transition temperature was almost independent of the shear rate. The SA –N transition temperature was also independent of the shear rate, but the transition peak was broadened by applying shear flow. For both transitions, the transition entropies were independent of the shear rate. These results suggest that the thermodynamic properties were not considerably changed by shearing because the molecular alignments in the domains were not substantially changed, whereas shearing changed the LC domain directions, which can be detected by viscosity and SAXS measurements.